Global clumped isotope foraminifer to temperature calibration data from Meinicke et al 2020, Geochimica et Cosmochimica Acta ... - Meinicke, Niklas; Ho, Sze; Hannisdal, Bjarte; Nürnberg, Dirk; Tripati, Aradhna; Schiebel, Ralf; Meckler, Anna (Interdisciplinary Earth Data Alliance (IEDA), 2020)
This global dataset contains D47, d18O and d13C data from 13 sites and 14 species of planktonic foraminifers used in a multi-species clumped isotope to temperature calibration. In addition, replicate-level raw data is provided to allow for reprocessing of the data. ... : Meinicke, N., Ho, S.L., Hannisdal, B., Nürnberg, D., Tripati, A., Schiebel, R. and Meckler, A.N. (2020) A robust calibration of the clumped isotopes to temperature relationship for foraminifers. Geochimica et Cosmochimica Acta 270, 160-183. ...